2020
DOI: 10.1186/s12936-020-03499-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bed net colour and shape preferences on bed net usage: a secondary data analysis of the 2017 Malawi Malaria Indicator Survey

Abstract: Background Malaria remains a significant cause of morbidity and mortality in the paediatric population in Malawi. Insecticide-treated bed nets are a key vector malaria control intervention, however, advancement towards universal access is progressing slowly. Malawi Malaria indicator surveys (MMIS) show diverse user preferences of bed net shape and colour. The objective of this work was to understand if bed net shape and colour preferences affect usage. Methods This is a secondary analysis of data from househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…However, the pregnant women never had guidance and education concerning ITN usage at the ANC clinic. These findings validate the findings of several other previous studies that also identified institutional factors that influenced ITN usage [4,19,[20][21][22][23][24][25][26][27][28][29].…”
Section: Discussion Of Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the pregnant women never had guidance and education concerning ITN usage at the ANC clinic. These findings validate the findings of several other previous studies that also identified institutional factors that influenced ITN usage [4,19,[20][21][22][23][24][25][26][27][28][29].…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…The findings of the current study indicated that the pregnant women felt heat and warmth when sleeping under the ITN, they itched and had rashes when sleeping under the ITN, they had difficulty in hanging their ITNs, and they also had difficulty in breathing when sleeping under the ITN. These findings concord with the findings of several other previous studies that also identified personal factors that influence the usage of ITNs among pregnant women [4,7,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Also, in two rural communities in the Greater Accra region of Ghana, a randomized control trial by found that more than 90% of respondents found ITNs to be uncomfortable to use because they trap heat, especially during warm weather or dry seasons where 75% of respondents could not sleep under an ITN without a fan.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…Conical-shaped LLINs were preferred and more likely to be used than rectangular ones in Ethiopia [ 12 , 13 , 21 ]. Bed nets that matched the preferred colour of individual users were more likely to be used in Malawi [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gaps may exist between policy and implementation [19], with human behaviour one of the most complex variables involved in malaria transmission. The local population might accept, but not use and maintain nets, use nets for other purposes or migrate to areas with higher malaria risk [20][21][22]. Further reasons include social factors, such as autonomy in health care decisions [23], bed net integrity and insecticide degradation [24].…”
Section: Introductionmentioning
confidence: 99%